X-ray Methods for analisis of condensed films - Malykhin, S. V.; Mikhailov, Igor; Borisova, Svitlana (Національний технічний університет "Харківський політехнічний інститут", 2025)
The monograph is devoted to X-ray methods for studying thin films. Thin films, coatings, thin-film layered systems are the basis of modern technologies of micro- and nanoelectronics, optoelectronics, X-ray optics and microscopy. The proposed monograph presents the most important results of studies of thin-film systems obtained using original X-ray methods. The monograph is recommended for teachers, graduate students and senior students of specialties related to solid state physics.
Keywords: monograph; condensed films; X-ray methods; nanoelectronics; optoelectronics; X-ray optics